BREAD, POWER, AND NEOLIBERAL MUNICIPALISM: THE HALK EKMEK A.Ş. AS A CASE OF BREAD AND CIRCUSES POLITICS - Emre Mete (Agora International Journal of Economical Sciences)
This article explains the historical process and political importance of Halk Ekmek A.Ş., a public bread production company, since its establishment. In this context, Halk Ekmek A.Ş. was considered an example of a Socialist Municipality in the past, but today, it is used as a political tool in neoliberal municipalism. Although municipal enterprises such as Halk Ekmek, which are taken as an example in this study, are generally presented as social enterprises, they have also become enterprises of profitability and political gain, especially as a result of neoliberal municipal practices. Bread is both a fundamental part of culture and nutrition for the Turkish people and a unique part of the control system in which the government is also involved. For this reason, public bread enterprises, such as Halk Ekmek A.Ş., are seen as valuable by those in power to control society and create a political argument. As a result of this examination, it will be investigated that this order established through public means is essentially a part of a "bread and circus" politics that appeases the public and strengthens the political power of the governments. As a result of the findings obtained, it will be seen how Municipality Participation can create a system that serves political purposes and kills competition. This study contributes to the public administration literature, where there are very few studies on this subject, by critically analysing how the socialist municipality period implemented in the historical process has essentially transformed into neoliberal municipal practices. As a result, the sustainability of this system will be questioned.